Avaliação da vulnerabilidade ambiental compreendendo sub-bacias da orla Sul da cidade de Belém/PA - MIRANDA, Inaiê Malheiros (2018)
The study of environmental vulnerability is an important cientific topic for environmental analysis of coastal zone, providing information about the stability of the ground, as regards to their behavior towards the morphogenesis and pedogenesis process and their interrelations with the pressures of human use and occupation. In view of this, the present work deals about the mapping of environmental vulnerability in areas that include the sub-basins on the southern shore of the city of Belém-PA (Tamandaré, Estrada Nova, Tucunduba and Murucutu), identifying areas of greatest environmental fragility and subdiving them into vulnerability classes (low, low average, average, high and very high) to assist in its coastal management. For this, was used with base tematic maps of geology, soil, terrain slope, and land use and cover, that was rastered and reclassified in the software ArcMap 10 into hierarchies categories of vulnerability index for each unit mapped, using empirical values of “1” (less vulnerable) to “5” (more vulnerable). From de analysis of environmental vulnerability map, it was observed in the study area the predominance of the class of high vulnerability in the region, corresponding to 36,71% of the study area, characterized mainly by the interaction of the Urban area land use class, in lithologic units of Pós-barreira sediments and great representation of the class of very high vulnerability, associated with the establishment of the Urban area land use class, in lithologic units of recent sediments, that include the floodplain of Guamá river, and, in regions with classes of terrain slope higher than 6%, both without vegetable coverage, including 21,27% of the study area. The process of urban occupation in areas with very high environmental vulnerability, located near the margins of sub-basins of Tamandaré, Estrada Nova e Tucunduba, happened irregularly, mainly on the shore of Estrada nova sub-basins, with the establishment of artificial structures for residential use, commercial and services activities, in classes of terrain slope lower than 2%, corresponding to the almost flat land, where the runoff is slow, causing environmental problems relating to flood and flooding in this region, while in the edge of the Tucunduba sub-basin, the fragility due the association of environmental aspects considered in this work, show your effects with the soil erosion process.